Asymmetric Reductive Carbocyclization Using Engineered Ene Reductases. Issue 24 (14th May 2018) - Heckenbichler, Kathrin; Schweiger, Anna; Brandner, Lea Alexandra; Binter, Alexandra; Toplak, Marina; Macheroux, Peter; Gruber, Karl; Breinbauer, Rolf
Abstract: Ene reductases from the Old Yellow Enzyme (OYE) family reduce the C=C double bond in α, β‐unsaturated compounds bearing an electron‐withdrawing group, for example, a carbonyl group. This asymmetric reduction has been exploited for biocatalysis. Going beyond its canonical function, we show that members of this enzyme family can also catalyze the formation of C−C bonds. α, β‐Unsaturated aldehydes and ketones containing an additional electrophilic group undergo reductive cyclization. Mechanistically, the two‐electron‐reduced enzyme cofactor FMN delivers a hydride to generate an enolate intermediate, which reacts with the internal electrophile. Single‐site replacement of a crucial Tyr residue with a non‐protic Phe or Trp favored the cyclization over the natural reduction reaction. The new transformation enabled the enantioselective synthesis of chiral cyclopropanes in up to >99 % ee . Abstract : Rational protein design led to ene reductase variants that serve as synthetically useful biocatalysts for the conversion of α, β‐unsaturated aldehydes and ketones into the corresponding cyclopropanes. This transformation proceeds with high catalytic efficiency and enantioselectivity and could be applied for a variety of substrates.